2010
DOI: 10.1007/s11605-010-1298-4
|View full text |Cite
|
Sign up to set email alerts
|

Tumors Arising at Previous Anastomotic Site may have Poor Prognosis in Patients with Gastric Stump Cancer Following Gastrectomy

Abstract: Follow-up programs after gastrectomy should account for long latency periods of disease. Early detection, attentive observation of anastomotic site, and sufficient surgical resection were important influences on outcome for patients with GSC after Billroth I or Billroth II reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…16 Previous studies have identified differences between cases of RGC arising following benign and malignant disease. 6,12,17,19,[25][26][27] In our study, as for other previous studies, the interval between first gastrectomy and the second surgery of RGC after benign disease was longer than that after malignant disease. 5,6,[16][17][18]22,26,28 RGC after benign disease is considered to originate from the exposure to duodenogastric reflux of bile and pancreatic There is an overlap in the number of organs with combined resection and recurrence M mucosa, SM submucosa, MP muscularis propria, SS subserosa, SE serosa-exposed, SI serosa-infiltrating a Statistically significant fluid.…”
Section: Discussionsupporting
confidence: 84%
“…16 Previous studies have identified differences between cases of RGC arising following benign and malignant disease. 6,12,17,19,[25][26][27] In our study, as for other previous studies, the interval between first gastrectomy and the second surgery of RGC after benign disease was longer than that after malignant disease. 5,6,[16][17][18]22,26,28 RGC after benign disease is considered to originate from the exposure to duodenogastric reflux of bile and pancreatic There is an overlap in the number of organs with combined resection and recurrence M mucosa, SM submucosa, MP muscularis propria, SS subserosa, SE serosa-exposed, SI serosa-infiltrating a Statistically significant fluid.…”
Section: Discussionsupporting
confidence: 84%
“…15,23 Lymphatic flow through anastomotic site is another cause of poor prognosis of RGC. Postoperative adhesion around anastomosis is the most important reason of lower rate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it remains controversial whether there is any difference in the prognosis between the malignant and benign groups. Previous studies have revealed contradictory results regarding the 5-year survival rates between initial surgery for benign disease and that for malignant disease (Table 5) [8,29,34,36,57]. No significant difference in the stage distribution was found between the two groups, except for one study; Takeda et al…”
Section: Is the Prognosis Of Rgc Different From That Of Primary Pgc?mentioning
confidence: 90%
“…In the eligible papers published after 2000, some articles reported the mean or median intervals between the initial surgery and RGC diagnosis. In particular, 7 studies reported the intervals stratified by RGC of the initial surgery for malignant or benign disease, although the background characteristics of patients varied substantially [23,26,28,[33][34][35][36]. The mean or median intervals between the initial surgery for malignant disease and RGC diagnosis seemed to be shorter than those between the initial surgery for benign disease and RGC diagnosis ( Table 1).…”
Section: Studies Included In the Present Articlementioning
confidence: 99%